2021
DOI: 10.3390/plants10040659
|View full text |Cite
|
Sign up to set email alerts
|

The Metabolite Profile in Culture Supernatant of Aster yomena Callus and Its Anti-Photoaging Effect in Skin Cells Exposed to UVB

Abstract: Aster yomena (A. yomena) extract has anti-inflammatory, antioxidant, anti-asthma, and anti-atopic effects. However, the commercial use of A. yomena extract requires a long processing time with specific processing steps (including heat treatment and ethanol precipitation), and there are various environmental problems. We aimed to build a system to produce A. yomena extract by culturing the callus in a bioreactor that can allow rapid process scale-up to test the effect of extract (AYC-CS-E) isolated from culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…Our group recently showed the effectiveness of AYC-P-E in improving various phenomena, such as skin damage, inflammatory reaction, decreased type I procollagen, and increased elastase, accompanied by photoaging in UVB-irradiated keratinocytes 22 . The present study aimed to evaluate the anti-melanogenic effects of the 19 metabolites present in AYC-P-E (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Our group recently showed the effectiveness of AYC-P-E in improving various phenomena, such as skin damage, inflammatory reaction, decreased type I procollagen, and increased elastase, accompanied by photoaging in UVB-irradiated keratinocytes 22 . The present study aimed to evaluate the anti-melanogenic effects of the 19 metabolites present in AYC-P-E (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, we recently observed that AYC-P-E exerts anti-photoaging functions in UVB-irradiated human keratinocytes by improving cell viability, inhibiting elastase, forming Type I procollagen, and inhibiting TNF-α. AYC-P-E is consists of 19 main metabolites including one isoflavonoid, one flavonoid, and three sphingolipids 22 . Among these, flavonoid compounds, such as isoflavonoids and flavonoids, have strong anti-oxidative, anti-carcinogenic, as well as anti-inflammatory effects 32 , 33 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations